DNA binding, antitubercular, antibacterial and anticancer studies of newly designed piano-stool ruthenium(ii) complexes - Navale, Govinda; Singh, Sain; Agrawal, Sonia; Ghosh, Chandrachur; Choudhury, Angshuman Roy; Roy, Partha; Sarkar, Dhiman; Ghosh, Kaushik (Dalton Transactions, 2022)
The chemotherapeutic potential of ruthenium(ii) complexes has recently attracted researchers' interest as antibacterial and anticancer agents. In this study, two novel half-sandwich imine-based Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6] (Ru-1) and [Ru(p-cymene)Cl(L-2)][PF6] (Ru-2)) were reported for their deoxyribonucleic acid (DNA) binding and antitubercular, antibacterial, and anticancer activities. The molecular structure of Ru-2 was obtained by single-crystal X-ray crystallography. DNA interaction studies were conducted by UV-Vis absorbance and fluorescence spectral titration which gave rise to DNA binding constants (K-b) of 1.32 x 10(6) and 1.82 x 10(6) for Ru-1 and Ru-2, respectively and the Stern-Volmer binding constant (K-SV) values for Ru-1 and Ru-2 were 1.7763 x 10(4) M-1 and 7.6 x 10(3) M-1, respectively. The in vitro antitubercular activity was evaluated against Mycobacterium tuberculosis H37Ra. The antibacterial potential of both the Ru-complexes was examined against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. The half-maximal inhibitory concentration (IC50) values for the antitubercular activity of Ru-1 and Ru-2 were 4.87 +/- 1.32 mu M and 5.78 +/- 0.54 mu M, respectively. A cytotoxic study of these complexes was performed against the human breast cancer cell line (MCF-7) and the human embryonic kidney cell line (HEK293) (normal cells). The study revealed meaningful activity of the Ru-1 complex against (cancer) MCF-7 cells, while the viability of HEK293 (normal) cells in the presence of Ru-2 was higher as compared to a reference drug 5FU. We suggest that these kinds of Ru-complexes could have potential for application in metallopharmaceuticals.